Numerical Investigation And Performance Analysis Of Photovoltaic Thermal PV/T Absorber Designs: A Comparative Study - Sachit, Fadhil Abdulameer; Mohd Rosli, Mohd Afzanizam; Tamaldin, Noreffendy; Misha, Suhaimi; Abdullah, Amira Lateef (Penerbit Akademia Baru, 2019)
The term of PV/T refers to the solar energy system which is associate the photovoltaic and solar collector with each other in order to improve the photovoltaic efficiency. This system generates both thermal and electrical energy simultaneously. The aim of this work is to investigate numerically and comparing the performance of PV/T system with two absorber designs. A new photovoltaic thermal (PV/T) collector called serpen-direct is designed and compared with serpentine PV/T design. Theoretically, the PV/T performance for serpen-direct flow is validated and compared with the conventional serpentine flow design using MATLAB Simulink. Parameters, such as outlet water temperature, cell temperature and PV and thermal efficiency, were tested under various mass flow rates that range from 0.01 kg/s to 0.1 kg/s and two-level solar irradiance 300 W/m2 and 700 W/m2. Results show that the serpen-direct flow absorber design provides a better system performance than the serpentine flow design under the same operating conditions. The maximum PV and thermal efficiencies are 12.51% and 57.66%, respectively, for the serpen-direct flow and 12.43% and 54.68%, correspondingly, for the serpentine flow design.